MOBILE APPLICATION FOR FATIGUE MANAGEMENT SYSTEM - NOORHISHAM, MUHAMMAD SYAFIQ (IRC, 2020)
This report intended to propose an Application that helps to improve ways of health handling which is Fatigue Management System (FMS). This application aims to enable all employee in numerous firm’s and organization to practice better way of handling fatigue workers through the proposed technology and application. This application also intended to serve needs to superiors in monitoring and tracking fatigue status of the employee, by identifying this, prevent in early stage could be done efficiently. This report will discuss whole necessity that relates to the information of fatigue management and how it could be implement through advancement of technology which able to serve purpose of handling fatigue worker nowdays. Starting from analyzing, brainstorming and also implementation of the project. Workplan and structure of the application also will be discussed in this report.